PROSES PELATIHAN LIFE SKILL MENJAHIT WARGA BELAJAR PENDIDIKAN KESETARAAN PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) ASSOLAHIYAH DESA PASIRJAYA KECAMATAN CILAMAYA KULON KABUPATEN KARAWANG - Imamil, Denis; Hidayat, Dayat; Suminar, Uum (Comm-Edu (Community Education Journal), 2025)
The purpose of this study was to obtain information about the process, results, as well as the inhibiting and motivating factors in the sewing life skills training program. The community education program implemented by PKBM Assolahiyah aims to empower coastal communities in the fields of education and entrepreneurship. PKBM Assolahiyah is a strategic and professional institution in managing and organizing sewing training courses in creating a professional workforce that has been given sewing skills and expertise. This research was conducted using a qualitative approach, the case study method, which involved one head of the institution, one educator/tutor, and one student/student. The data from this study were obtained from observations, interviews, and documentation. In qualitative research, the stages involved include the orientation stage, the exploration stage, and the member check stage. The results of this study indicate that the answers from the interviews about the sewing life skill training process including planning and implementation are carried out properly. Program planning is prepared by managers and also tutors/educators at the beginning of the academic year by adjusting the required training programs and given to students/learning residents in accordance with the equality education curriculum that must carry out empowerment. While the implementation of the program is in accordance with the aim of empowering the surrounding community. One of the main supporting factors in maximizing sewing life skill training programs. Human resources as learning citizens are an inhibiting factor in the implementation of these program activities due to their minimal participation. Keywords: Training, Learning Center for Community, Life Skills.